A study of the quality standards of some selected small-scale local garment manufacturers in Baclaran - Zerda, Maria Zorayda Preciosa Moran; Dizon, Angelitan Mendoza (1993.)
The purpose of the study is to determine the conformity of the product quality standards of small scale local manufacturers to set government standards and to publish quality standards for consumers. Respondents have been limited to one major bulk buying center, Baclaran and the product line have been limited to ladies ready-to-wear garments. The study made use of questionnaires, Product Quality Surveys (PQS), interviews and plant visits in its data gathering. Major findings showed that the quality standards of some small scale local garment manufacturers do not conform to the Bureau of Product Standards Labeling Code. Although the threads they used are licensed to use the PS quality mark. Results also showed that when their products are subjected to final quality audits using the Military standard 1050, the samples would be rejected and considered as second class products. Results also show that there is an average of two defect per garment with a large percentage found to be classed as major defects. Their average measurement differences resulted with an acceptable tolerance level for their products based on the guideline published by the Philippine Trade Training Center.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing factories -- Philippines